Sistem Penghitung Berat Gabah Berbasis Desktop - Herman, Herwin; Basri, Muhammad; Suwardoyo, Untung (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2024)
One of the interesting things to examine is the way farmers measure their grain harvest using scales. The reality in the field is that weighing is sometimes not accurate regarding the weight of certain types of grain. Actors in the field sometimes cheat by tampering with analog scales. Based on this problem, researchers conducted research to create a digital grain weight calculation application. The research was carried out by creating a digital weighing application that uses Arduino Uno as a microcontroller, load cell and HX711 module. The system is equipped with a desktop-based application to manage grain sales calculations based on weight. Testing is carried out by comparing measurement results between digital scales and the designed system. The test results show that the designed system can carry out measurements with an accuracy level of up to 90%